Avaliação reprodutiva de camundongos da linhagem NOD (Non-Obese Diabetic) - Navarezi, Amanda Godoi (2022)
The demand for new experimental models grows proportionately as pre-clinical tests need more refined and reproducible results, thus also contributing to one of the main concepts in Laboratory Animal Science: the 3 Rs, which are the reduction of animals in research, refined biomodels and techniques who seek to alleviate stress and discomfort, and replacement of experimental models with validated alternative techniques. An example of a biomodel created in the laboratory is the NOD mice (Nonobese Diabetic), which has contributed mainly to research involving type 1 diabetes mellitus, since the autoimmune process occurs in a very similar way to humans, in addition to several other areas that can be studied from this experimental model. With this in mind, the UFMS Central Animal Facility received NOD couples, which were established in the Breeding Area, where they are produced for supply to the Institution's researchers. With the establishment of this new strain, the present work sought to evaluate the reproduction of NOD mice, mated in the breeding colony, and in obtaining oocytes and embryos with and without hormonal stimulation. Data from 4 births of 20 couples kept in intensive monogamous mating system in the breeding area were used to calculate the productivity indexes. To obtain oocytes and embryos, the Whitten effect was used to synchronize estrus in all females in the study. The hormonal protocol was performed in 20 females through the administration via IP of 7.5IU of PMSG on day 0, and 48 hours later 7.5IU of hCG followed by mating of 10 females with vasectomized males (n=10) to obtain oocytes and the other 10 with intact males (n=10) to obtain embryos. On day 4, the presence of vaginal tampons and oocyte collection were observed. On day 5, embryos were collected. The same mating procedure was performed for the group of females without hormonal stimulation (n=40). In the breeding colony, a litter average of 7.50±0.68 was observed; 5.25±0.95; 2.85±0.88 and 2.20±0.73, from the first to the fourth delivery, respectively. In females that did not receive hormonal stimulation, an average of 6.25±1.15 oocytes and 2.90±0.86 embryos in the 2-cell phase (D2) were obtained, while the superovulated females obtained 79.20±8.43 oocytes and 19.90±7.90 D2 embryos. Regarding the percentage of viable embryos (D2) over the total number of embryos observed, the natural group obtained an average of 20.74±6.27 and the group of superovulated females presented 24.71±6.26. Thus, it was concluded that in intensive monogamous mating, the NOD strain shows a significant drop from the third parturition, and they present a satisfactory response to superovulation in terms of the number of oocytes and embryos, but in relation to the percentage of viable embryos there was no significant difference between groups. Therefore, superovulation is a viable option for obtaining oocytes and embryos with a reduced number of animals, being an important tool for the creation of a germplasm bank and assisted reproduction of the NOD strain. Descriptors: superovulation; Inbred NOD Mice; animal mating behavior; oocytes; mammalian embryo.